simplify
7{[5(b-4+16]-[3(4b-3)+4]}=
3 answers
Where is the ) that matches the ( before the b-4?
start with the innermost brackets
7{[5(b-4+16]-[3(4b-3)+4]}
=7{[5(b-12]-[12b-9+4]}
= 7{[5b-60]-[12b-5]}
= 7{5b-60-12b+5}
= 7{5b-60-12b+5}
= 7{-7b - 55}
= -49b - 385
7{[5(b-4+16]-[3(4b-3)+4]}
=7{[5(b-12]-[12b-9+4]}
= 7{[5b-60]-[12b-5]}
= 7{5b-60-12b+5}
= 7{5b-60-12b+5}
= 7{-7b - 55}
= -49b - 385
bobpursely is right.
I should have looked at your brackets more carefully
I should have looked at your brackets more carefully